941 The Effect of COVID-19 on Orthopaedic Trauma Theatre Efficiency and Surgical Training in the North and East of Scotland Major Trauma Centres – a Year On. (19th August 2022) - Lim, JW; Lindsay, E; Rehman, H; Tong, EYH; Ammen bin Badekrizaman, M; Withall, A; Dalgleish, S; Mitchell, M; Boddie, D
Abstract: Aim: To determine the orthopaedic trauma theatre efficiency in two large major trauma centres (MTCs) in Scotland before and after the outbreak of Coronavirus disease (COVID-19) pandemic. Method: All trauma patients presented to the North and East of Scotland's MTCs prior to the outbreak of COVID-19 (7th May to 7th June 2019), during the first peak of COVID-19 (7th May to 7th June 2020), after Aerosol Generating Procedures updates (7th November to 7th December 2020) and the 'new normal' (7th May to 7th June 2021) were retrospectively reviewed. Training opportunities and theatre time were compared. The Kruskall-Wallis test was used. Results: There were no significant differences in the length of hospital stay (p=0.117, 0.065) and time from injuries and surgery within groups in both MTCs (p=0.508, 0.384). The pandemic has negatively affected the anaesthetic and surgical preparation time, time between end of procedure and send for next case, and turnover time, with more profound effect on the North of Scotland's MTC. The trainee's involvement as main surgeon had decreased with the outbreak of the pandemic, with the junior trainees being affected most severely in North of Scotland. The time taken for patient to arrive to theatre after sending and total downtime were twice as long in the North of Scotland. Conclusion: The COVID-19 pandemic has negatively impacted the orthopaedic trauma theatre efficiency and training opportunities. Actions should be taken to improve the turnover time to maximise theatre efficiency while prioritizing training opportunities.